Clinical, Laboratory, Cytometry and Cytogenetic Characteristics of a Cohort of Patients Dianosed with Multiple Myeloma for the First Time in a Third-Level Hospital in Medellín, Colombia, Survival after 8 Years of Follow-Up (2023)
ABSTRACT: Background: Multiple myeloma is the second most common hematologic malignancy after lymphomas. Few studies have characterized significant and full variables at the time of diagnosis of multiple myeloma in Colombia, and there is no data evaluating patients for follow-up. Materials and Methods: A retrospective cohort study is presented, describing the clinical, laboratory, cytometric, and cytogenetic characteristics of patients with a de novo diagnosis of multiple myeloma evaluated in a reference hematology laboratory attached to a highly complex hospital in Medellín, Colombia. We follow them until death as a main outcome. Results: A total of 170 patients with a de novo diagnosis of multiple myeloma were collected from a database of 421 patients with different monoclonal gammopathies. Mainly, it was found that 50.8% of the patients were men; the median age was 62 years; 65.4% had secretion of the IgG kappa; half of the patients presented International Staging System (ISS) Stage III. The β2 macroglobulin >4 mg/L and creatinine >2 mg/dl were the main variables significantly associated with survival (Hazard Ratio (HR) 2.4 and 2, respectively). Eighty-five percent of patients presented with bone lytic lesion involvement and less than 3% with extramedullary involvement. Conventional Banding Karyotype (CBK) genetic risk assessment yield was poor, compared with although scarce data regarding Cytogenetic risk assessment based on Fluorescence in-situ Hybridization (FISH). Conclusion: The clinical profile of the patients with a de novo diagnosis of multiple myeloma in our cohort is similar to that described in international studies. The diagnosis of multiple myeloma was documented at younger ages, with more advanced stages, anemia, and a high percentage of bone disease. ISS provides an excellent tool for prognosis purposes. Cytogenetic risk assessment based on FISH should be done for all MM patients from therapeutic implications. We need standardized protocols for bone marrow sample manipulation and processing in order to guarantee good correlation for plasma cells count methods.